2015
DOI: 10.2217/pgs.15.22
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Pharmacists’ Perception on the Use of Pharmacogenomic Testing in the Mental Health Population

Abstract: Aim: Pharmacogenomics could play a role in improving patient care, reducing adverse drug reactions and overall healthcare costs. However, whether it is utilized may be determined by how it is perceived by healthcare professionals, including pharmacists. Methods: A cross-sectional web-based survey evaluated psychiatric pharmacists’ use, knowledge and perception of the effectiveness of such testing. Results: Among participants, 80% worked at sites not offering pharmacogenomic testing, mostly due to a lack of fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 9 publications
0
27
0
2
Order By: Relevance
“…How ever, there were concerns about potential overreliance on the tests and the length of time it took to receive the results. Shishko et al [5] surveyed 107 psychiat ric pharma cists from the College of Psychiatric and Neuro logic Pharmacists, and found that there was a lack of availability and understanding regarding the use of pharmacogenomics.…”
Section: Clinicians' Perceptions Of Pharmacogenomics Use In Psychiatrymentioning
confidence: 99%
See 1 more Smart Citation
“…How ever, there were concerns about potential overreliance on the tests and the length of time it took to receive the results. Shishko et al [5] surveyed 107 psychiat ric pharma cists from the College of Psychiatric and Neuro logic Pharmacists, and found that there was a lack of availability and understanding regarding the use of pharmacogenomics.…”
Section: Clinicians' Perceptions Of Pharmacogenomics Use In Psychiatrymentioning
confidence: 99%
“…Despite these benefits, the adoption of pharmaco genomics in clinical practice has been suboptimal and perceptions of psychiatrists toward this technology have been cited as a significant barrier. A review of the literature identified only four studies [2][3][4][5] which examined the attitudes of psychiatrists toward pharmaco genomic testing. However, they were mostly done in locations where pharmacogenomic testing was already commonly used.…”
mentioning
confidence: 99%
“…Adding the adjustment of therapy according to genetics would fit their specialization [11,15]. However, a limited number of studies have evaluated pharmacists' knowledge in pharmacogenetics and their willingness to manage these tests [17,18,19,20,21]. Amongst these studies, de Denus et al surveyed the opinions and concerns of Quebec pharmacists toward pharmacogenetics.…”
mentioning
confidence: 99%
“…Most of the studies26-29 that have been conducted were at practice sites already familiar with and utilizing pharmacogenomic testing. A recent study29 surveying psychiatric pharmacists showed only 36% considered themselves knowledgeable in pharmacogenomics, and 80% worked at sites that did not offer the testing due to lack of funding. Another recent study30 was conducted in Singapore, which only routinely tests for HLA-B*1502 prior to carbamazepine initiation.…”
Section: Discussionmentioning
confidence: 99%